"Pigmented Extramammary Paget Disease"—A Potential Mimicker of Malignant Melanoma and a Pitfall in Diagnosis: A Case Report and Review of the Literature. (January 2019) - Kiavash, Katrin; Kim, Steve; Thompson, Andrew D.
Abstract : Abstract: Extramammary Paget disease (EMPD) is a rare intraepithelial carcinoma and an uncommon variant of Paget disease affecting areas of the apocrine-rich skin of the perineum, vulva, and less commonly, axilla. Women in their sixth to eighth decades are commonly affected. It is exceedingly rare for EMPD to present on the face, chest, abdomen, or other nonapocrine sites and even more unusual for EMPD to present as a pigmented lesion. The relationship between Paget cells in pigmented extramammary Paget disease (PEMPD) and reactive proliferation and colonization by melanocytes has been poorly explored. The relevance of this rare entity resides in its potential to be misdiagnosed clinically and histopathologically as malignant melanoma in situ. Therefore, application of a panel of immunostains and careful analysis and interpretation of these findings are essential to arrive at the correct diagnosis. We report a new case of PEMPD on a nonapocrine site. The specimen was examined by routine microscopy including hematoxylin and eosin stain as well as immunostains. Histologic examination revealed characteristic features of PEMPD confirmed with immunohistochemical stains.